On the interdependence of ketone body oxidation, glycogen content, glycolysis and energy metabolism in the heart. (1st March 2023) - Kadir, Azrul Abdul; Stubbs, Brianna J.; Chong, Cher‐Rin; Lee, Henry; Cole, Mark; Carr, Carolyn; Hauton, David; McCullagh, James; Evans, Rhys D.; Clarke, Kieran
Abstract : Abstract: In heart, glucose and glycolysis are important for anaplerosis and potentially therefore for d ‐β‐hydroxybutyrate (βHB) oxidation. As a glucose store, glycogen may also furnish anaplerosis. We determined the effects of glycogen content on βHB oxidation and glycolytic rates, and their downstream effects on energetics, in the isolated rat heart. High glycogen (HG) and low glycogen (LG) containing hearts were perfused with 11 mM [5‐ 3 H]glucose and/or 4 mM [ 14 C]βHB to measure glycolytic rates or βHB oxidation, respectively, then freeze‐clamped for glycogen and metabolomic analyses. Free cytosolic [NAD + ]/[NADH] and mitochondrial [Q + ]/[QH2 ] ratios were estimated using the lactate dehydrogenase and succinate dehydrogenase reaction, respectively. Phosphocreatine (PCr) and inorganic phosphate (Pi ) concentrations were measured using 31 P‐nuclear magnetic resonance spectroscopy. Rates of βHB oxidation in LG hearts were half that in HG hearts, with βHB oxidation directly proportional to glycogen content. βHB oxidation decreased glycolysis in all hearts. Glycogenolysis in glycogen‐replete hearts perfused with βHB alone was twice that of hearts perfused with βHB and glucose, which had significantly higher levels of the glycolytic intermediates fructose 1, 6‐bisphosphate and 3‐phosphoglycerate, and higher free cytosolic [NAD + ]/[NADH]. βHB oxidation increased the Krebs cycle intermediates citrate, 2‐oxoglutarate and succinate, the total NADP/H pool, reduced mitochondrial [Q + ]/[QH2 ], and increased the calculated free energy of ATP hydrolysis (∆ G ATP ). Although βHB oxidation inhibited glycolysis, glycolytic intermediates were not depleted, and cytosolic free NAD remained oxidised. βHB oxidation alone increased Krebs cycle intermediates, reduced mitochondrial Q and increased ∆ G ATP . We conclude that glycogen facilitates cardiac βHB oxidation by anaplerosis. Key points: Ketone bodies (d ‐β‐hydroxybutyrate, acetoacetate) are increasingly recognised as important cardiac energetic substrates, in both healthy and diseased hearts. As 2‐carbon equivalents they are cataplerotic, causing depletion of Krebs cycle intermediates; therefore their utilisation requires anaplerotic supplementation, and intra‐myocardial glycogen has been suggested as a potential anaplerotic source during ketone oxidation. It is demonstrated here that cardiac glycogen does indeed provide anaplerotic substrate to facilitate β‐hydroxybutyrate oxidation in isolated perfused rat heart, and this contribution was quantified using a novel pulse–chase metabolic approach. Further, using metabolomics and 31 P‐MR, it was shown that glycolytic flux from myocardial glycogen increased the heart's ability to oxidise βHB, and βHB oxidation increased the mitochondrial redox potential, ultimately increasing the free energy of ATP hydrolysis. Abstract : Abstract figure legend Overview of relationship of glycogen to ketone body oxidation and cardiac energetics in isolated perfused rat hearts. Myocardial glycogen was pre‐labelled with tritium and its metabolic fate tracked using a pulse–chase technique. Increased glycolytic flux from glycogen facilitated increased exogenous β‐hydroxybutyrate (βHB) oxidation through anaplerosis, and the increased βHB oxidation increased mitochondrial redox potential, and hence increased free energy of ATP hydrolysis.